Characterizing unique supportive care needs among women living with metastatic breast cancer: A qualitative study. Issue 1 (23rd January 2023) - Moreno, Patricia I.; Noriega Esquives, Blanca; Thomas, Jessica L.; Horner, Fiona S.; Torzewski, Joanna B.; Gradishar, William; Victorson, David; Penedo, Frank J.
Abstract: Background: Women with metastatic breast cancer face unique challenges as they cope with life-limiting prognoses and arduous treatments. However, the vast majority of research has focused on optimizing quality of life in women with early-stage, nonmetastatic breast cancer and little is known about supportive care needs among women living with metastatic cancer. As part of a larger project that sought to inform the development of a psychosocial intervention, the aim of this study was to characterize supportive care needs among women with metastatic breast cancer and elucidate challenges unique to living with a life-limiting prognosis. Methods: Four, 2-hour focus groups with 22 women were audio-recorded, transcribed verbatim, and analyzed in Dedoose using a general inductive approach to code categories and extract themes. Results: A total of 16 codes emerged from 201 participant comments regarding supportive care needs. Codes were collapsed into four supportive care need domains: (1) psychosocial, (2) physical and functional, (3) health system and information, and (4) sexuality and fertility needs. The most prevalent needs were breast cancer–related symptom burden (17.4%), lack of social support (14.9%), uncertainty (10.0%), stress management (9.0%), patient-centered care (7.5%), and sexual functioning (7.5%). More than half of needs (56.2%) were in the psychosocial domain, and more than two-thirds of needs (76.8%) were in the psychosocial and physical and functional domains. Supportive care needs unique to living with metastatic breast cancer included the cumulative effects of continuously undergoing cancer treatment on symptom burden, worry from scan-to-scan regarding response to cancer treatments, diagnosis-related stigma and social isolation, end-of-life concerns, and misconceptions regarding metastatic breast cancer. Conclusions: Findings suggest that women with metastatic breast cancer have unique supportive care needs compared with women with early-stage breast cancer that are specific to living with a life-limiting prognosis and are not typically captured in existing self-report measures of supportive care needs. The results also highlight the importance of addressing psychosocial concerns and breast cancer–related symptoms. Women with metastatic breast cancer may benefit from early access to evidence-based interventions and resources that specifically address their supportive care needs and optimize quality of life and well-being.